Teacher’s Job Security and Workload Factors Affecting Job Satisfaction of Teachers in Multan (Southern Punjab)–Pakistan - Fawad Hussain; Amir Saif (Journal of Education and Vocational Research, 2019)
The educational system in any country plays a vital role for the development and achieving infrastructural goals. Pakistan since last few decades is facing critical economic and developmental challenges. The nature of work conditions in public and private organizations are getting more intensified and employees are facing critical time in term of workload, job security and satisfaction issues. This study is aiming to investigate the relationship between job security and workload factors influencing teacher’s job satisfaction. This paper has use SMART-PLS-SEM to examine the data using quantitative research techniques. The study was conducted among 266 teachers. The teachers’ job satisfaction was determined by two separate measures namely the teacher’s job security and workload influencing teacher’s job satisfaction. This study was trigged as teachers in higher education institutions were facing challenges regarding their job security and workload. The outcome exposed that there is an important relationship among teachers job security, workload, and teacher job satisfaction. The effects of these factors call further research. There is prerequisite to carry out a similar but comparative study in rural settings. In addition, it is very important to comprehend the significance of teachers’ job satisfaction where the industry is so uncertain. There is a need to address job satisfaction and workload stress with appropriate assessment such as rating system and teachers’ satisfaction index evaluation according to the tasks and work pressure allocated to each and every teacher. This reach adds value to knowledge by making universities, institutes and colleges administration to know the causes of teachers’ uncomfortable zone regarding their job security and workload. Conversely, it is also important for the administration in these institutes to well understand the needs and demands of their teachers and what factors will contribute to their satisfaction.